Peri-Operative Anaphylaxis Management - Komail Wasel Alamer; Murtadha Abdulkarim Alrushaydan; Khalid Jawad Alhaddad; Qassem Habib Bu Sbih; Muntathir Khalifah Alomayshi3; Abdullah Saud Alismail; Abdulkareem Abdullah Abdullah Alsubi; Ahmed Naji Al Yousif; Mahdi Abduallah Al Sultan; Amnah Ibrahim Alrasheed; Alshulayyil Abdulaziz Khalid A (International Journal of Scientific Research and Innovative Studies, 2022)
Peri-operative anaphylaxis is a rare but potentially life-threatening complication of anesthesia, requiring prompt recognition and intervention. By providing real-time feedback on ventilation and perfusion, EtCO2 monitoring can aid in the early identification of anaphylactic shock and guide resuscitative efforts. Adrenaline remains the cornerstone of treatment for anaphylaxis, and titration of adrenaline dosing based on clinical response and EtCO2 levels may help prevent under- or over-dosing. This review discusses the evidence supporting the use of EtCO2 monitoring and adrenaline titration in the management of peri-operative anaphylaxis and provides practical recommendations for their implementation in clinical practice. Key words : EtCO2, adrenaline, anaphylaxis.